If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -4) + 8 = 3(x + 8) Reorder the terms: 5(-4 + x) + 8 = 3(x + 8) (-4 * 5 + x * 5) + 8 = 3(x + 8) (-20 + 5x) + 8 = 3(x + 8) Reorder the terms: -20 + 8 + 5x = 3(x + 8) Combine like terms: -20 + 8 = -12 -12 + 5x = 3(x + 8) Reorder the terms: -12 + 5x = 3(8 + x) -12 + 5x = (8 * 3 + x * 3) -12 + 5x = (24 + 3x) Solving -12 + 5x = 24 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -12 + 5x + -3x = 24 + 3x + -3x Combine like terms: 5x + -3x = 2x -12 + 2x = 24 + 3x + -3x Combine like terms: 3x + -3x = 0 -12 + 2x = 24 + 0 -12 + 2x = 24 Add '12' to each side of the equation. -12 + 12 + 2x = 24 + 12 Combine like terms: -12 + 12 = 0 0 + 2x = 24 + 12 2x = 24 + 12 Combine like terms: 24 + 12 = 36 2x = 36 Divide each side by '2'. x = 18 Simplifying x = 18
| 2x+x^2-195=0 | | X+(8-56x)=45 | | 0.25x-0.4=0 | | -0.55x-0.33=0 | | -7x+15=0 | | 10x^2y+15xy^2=0 | | -3(j+6)=2-4j | | 2x+18=4x-4.3 | | 8x+12+7x-12=90 | | 4x-2=2(2x+5) | | 0.46x+2.8=0 | | -5+4y=-10 | | 4x-11=0 | | 2n^3+3n^2-2n-5967=0 | | -9x-6=0 | | y=-(1/8)x | | 7x+6=9+4x | | -5t^2+6t-1=0 | | y=-(1/8) | | 0.55x+0.33=0 | | y=3y^2-8y+2 | | 5x-12+2x=4+7x-16 | | y=3y^2-8+2 | | X-1/3x-7 | | 6f+17=47 | | 4x+16-2=1 | | 3(x-22)+3(x-4)=30 | | 9x^3-13x=-4 | | 4/7x-8/4=0 | | 49.61/6.05 | | 2x+122=9 | | 63=21w |